Impact of Sandium Mining on Social Economic and Ecology of River Region Lukulo Kebumen Central Java - Arsal, Thriwaty (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
This study aims to explain the impact of sand mining on socio-economic and ecological communities of the Lukulo River region. This research was conducted in Gemeksekti Village, Kebumen Regency, Central Java. Data collection is done through observation and interview and then analyzed qualitatively to explain research data and facts. The findings: (1) the impact of sand mining on the socio-economic of the river basin shows several aspects such as the loss of river social function which has been a public space as a means to communicate and social activities. Communications initially interwoven in the river, are now lost, and no activity is done other than sand mining, even communications with villagers across the river are cut off. Youth and children are deprived of playgrounds that have an impact on the socio-economic activities of the community, (2) the impact of sand mining on the ecological damage of rivers such as river widening and river water depths, river bank cliffs, polluted waters of diesel and oil, the loss of the river's pereng and several residents' rice fields.